Strategi Guru Tahfidz Dalam Meningkatkan Kemampuan Menghafal Al-Qur’an Pada Peserta Didik di MTs Ihyaul Ulum Dukun Gresik - Chilmi Illiyina Urfa; Moch Faizin Muflich (Universitas Islam Lamongan, 2024)
This research entitled Strategies of Tahfidz Teachers in Improving Students' Ability to Memorize the Qur'an at MTs Ihyaul Ulum Dukun Gresik uses qualitative research. The aim of this research is to find out the strategies of Tahfidz teachers in improving students' memorization abilities, knowing the supporting factors. and factors inhibiting the implementation of tahfidz teachers in improving the ability to memorize the Al-Qur'an, and solutions for tahfidz teachers in solving barriers for students to memorize the Al-Qur'an at MTs Ihyaul Ulum Dukun Gresik. The results of this research, (1) the tahfidz teacher's strategy in improving students' memorization skills include planning the tahfidz program, time for memorizing the Al-Qur'an, memorization methods, routine sema’an, memorization exams each semester, supervision and evaluation of the tahfidz program. Tahfidz program planning has been around since the founding of the program, but once a year a plan is always held to plan targets for the next year. The memorization time which has 2 specific times, namely 6 hours a day for 4 hours, starts at 07.00-09.30 and 2 hours at 10.30-11.30. The memorization method uses 3 methods, namely: the wahdah method, the muroja'ah method and the jama method. This routine must be done once a month by reading at least 5 Juz which the students have memorized together with the Tahfidz teacher. Memorization exams every semester In every semester, students are required to take a rote exam, that is, deposit all the memorization that has been obtained within 3 months. Regarding supervision or evaluation of the tahfidz program, namely always conducting evaluations once a month with fellow tahfidz teachers and madrasa heads, always controlling students through class attendance books or journal notes and always collaborating with the student's parents, namely sending photos/documentation of the students' achievements to the guardian. students via the WhatsApp group, and also share print outs of the results of students' memorization achievements which are attached to each student's report card.(2) the strongest supporting factor is the motivation that every student has from the start of entering the tahfidz program and the addition of motivation from the ustadz/ustadzah is also very supportive in improving the students' ability to memorize. Meanwhile, the inhibiting factors are more internal constraints, namely time, the busy activities both at the boarding school and at school affect the discipline of students who will be lazy in memorizing. (3) The Tahfidz teacher's solution in solving students' obstacles to memorizing the Al-Qur'an is by using an individual approach to students, always providing encouragement, motivation, giving them time and memory